2021
DOI: 10.1056/nejmoa2115624
|View full text |Cite
|
Sign up to set email alerts
|

BNT162b2 Vaccine Booster and Mortality Due to Covid-19

Abstract: Background The emergence of the B.1.617.2 (delta) variant of severe acute respiratory syndrome coronavirus 2 and the reduced effectiveness over time of the BNT162b2 vaccine (Pfizer–BioNTech) led to a resurgence of coronavirus disease 2019 (Covid-19) cases in populations that had been vaccinated early. On July 30, 2021, the Israeli Ministry of Health approved the use of a third dose of BNT162b2 (booster) to cope with this resurgence. Evidence regarding the effectiveness of the booster in lowering m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
290
3
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(317 citation statements)
references
References 15 publications
17
290
3
7
Order By: Relevance
“…Based on their observation they administered a booster dose and demonstrated protection against COVID-19. 6,7 Our results suggest that enumerating antibody titres at 6 months especially in those with comorbidities would help in prioritizing such individuals for booster dosing…”
Section: Discussionmentioning
confidence: 85%
“…Based on their observation they administered a booster dose and demonstrated protection against COVID-19. 6,7 Our results suggest that enumerating antibody titres at 6 months especially in those with comorbidities would help in prioritizing such individuals for booster dosing…”
Section: Discussionmentioning
confidence: 85%
“…However, the antibody levels decline, and the surveillance of vaccine effectiveness and the decline of immune responses highlighted the need for a vaccine booster doses in the first group of vaccinees who received the vaccine with a 3-week interval 7,8 . Initial studies have shown that a third dose of COVID-19 vaccines strongly boost the waning immune responses and on the population level reduce severe COVID-19-associated morbidity and mortality [9][10][11] . Decisions for the third vaccine dose have been further promoted by the emergence of new SARS-CoV-2 variants-of-concerns (VOCs).…”
Section: Introductionmentioning
confidence: 99%
“…With the omicron variant rising in several countries, the demand for boosters has been increasing. Prior to the emergence of the omicron variant, countries with excellent vaccination programmes used data that indicated a waning of vaccine effectiveness against infection and symptomatic disease with the delta variant to make the case for booster doses for their populations [ 1 ], an approach that has been amplified with the new variant.…”
mentioning
confidence: 99%
“…Data from Israel, which exclusively used the Pfizer vaccine showed initial very high levels of protection against death, severe disease, all symptomatic infection and all infection. This protection declined with time, particularly with the delta variant, prompting Israel to begin booster doses with the same vaccine in July 2021, raising protection to high levels again [ 1 ]. In the UK, data with both Astra Zeneca and Pfizer vaccine showed similar high initial protection but a decline of about 15% against severe disease over time with the delta variant [ 4 ].…”
mentioning
confidence: 99%